Implementation of Automatic Plant Sprinkler Control System in RT 07 RW 08 Pabuaran Mekar Subdistrict, Cibinong, Bogor - Reza Diharja; Wike Handini; Sri Wiji Lestari; Nur Witdi Yanto (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
The COVID-19 pandemic is forcing humans to adapt and be more creative. The Women Farmers Forum (KWT) group in Pabuaran Mekar receives assistance for the success of the food security program in the form of P2L (Sustainable Food Courts). The purpose of the program is to ensure that the community receives quality food from its own environment to maintain and improve the nutrition of the surrounding community. The problems faced in KWT are watering plants that still rely on humans, which is carried out in the morning and afternoon. The manufacture of an automatic plant sprinkler control system reduces the role of humans because it is equipped with a timer program. Users need to know about how to use the system to make it more durable and it is given from a presentation that is aimed as training. The survey at the end of the presentation provided feedback that the activities carried out were very good with a score of 65% of respondents in terms of more than the presentation material, and 79% of respondents rated it very much in accordance with their benefits and expectations. More than 87.5% of the respondents scored an excellent overall quality of the activities.